2022
DOI: 10.3390/app12136408
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Diversification of Cryptocurrency Portfolios: A Composite Copula-Based Approach

Abstract: This paper focuses on the selection and optimisation of a cryptoasset portfolio, using the K-means clustering algorithm and GARCH C-Vine copula model combined with the differential evolution algorithm. This integrated approach allows the construction of a diversified portfolio of eight cryptocurrencies and determines an optimal allocation strategy making it possible to minimize the conditional value-at-risk of the portfolio and maximise the return. Our results show that stablecoins such as True-USD are negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…They find that the best risk–return ratio (return 0.46%, risk 5.56%) is from the cluster with an average level of international diversification. Tenkam et al [ 22 ] use the K-means clustering algorithm and the GARCH C-Vine copula model to explore the diversification benefits of a portfolio comprising the 100 largest cryptocurrencies. They find a negative correlation between stablecoins and other cryptocurrencies, implying that they have the potential to be a haven during market instability for cryptocurrency holders.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They find that the best risk–return ratio (return 0.46%, risk 5.56%) is from the cluster with an average level of international diversification. Tenkam et al [ 22 ] use the K-means clustering algorithm and the GARCH C-Vine copula model to explore the diversification benefits of a portfolio comprising the 100 largest cryptocurrencies. They find a negative correlation between stablecoins and other cryptocurrencies, implying that they have the potential to be a haven during market instability for cryptocurrency holders.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Tenkam et al [31], the crypto market in 2009 spawned a diversification of digital financial portfolios that was efficiently spread across financial market classes. A diverse price distribution promotes investors' assessment of the risk management of their crypto portfolio in terms of calculating risk with a return on wealth proportional to the number of assets invested.…”
Section: The Relationship Of Investment Weight Price Period To Crypto...mentioning
confidence: 99%
“…Tenkam et al [31] found that diversified digital financial distribution leads to growth results by investors in managerial portfolio risk, with a rate of return from investment weights that can produce 80% of each crypto coin asset selection.…”
Section: The Interpretation Of Ols Modelmentioning
confidence: 99%
See 2 more Smart Citations